ANALISIS PENGARUH FAKTOR-FAKTOR MOTIVASI KERJA TERHADAP KEPUASAN KERJA PADA PEMBUDIDAYA IKAN DI KABUPATEN BANTUL, YOGYAKARTA - , CHATRINA S.T. SINAGA, Dr. Ir. Didik Purwadi, M.Ec. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Generally fish cultivation business activities conducted in groups. The fish farmers joined in a assosiation called Pokdakan (Kelompok Pembudidaya Ikan). Every business is required to optimize human resources and how human resources are managed. Human resources management can not be separated from factors that workers are expected to work as good as possible to achieve the goal. Labor is a major asset in a business activity and strategic role is as a thinker, planner and controller activity. In this case, the effort is meant is Pokdakan (Kelompok Pembudidaya Ikan) and the fish farmers who joined in it. This research was conducted with 2 Factor Theory Herzberg's approach is to identify the motivational factors become X variables (motivator factors and hygiene factors) and Y variable (job satisfaction). Retrieval of data using questionnaires distributed to the fish farmers in Bantul District. The results obtained from the research is from 11 variables found that 2 motivation variables that significantly influence job satisfaction. They are responsibility variable (beta coefficient is 2.453) and quality supervisor (Leader of Pokdakan) with beta coefficient is 2.194. Thus the motivation variable most dominant influence on job satisfaction is the responsibility variable. Influence factors contribution of the whole motivation on job satisfaction is 24,6%, while the rest is influenced by others factor motivation.